CIRCADIAN VARIATION IN THE ONSET OF ACUTE PULMONARY EDEMA IN DIABETIC AND NONDIABETIC PATIENTS - Ahmed, Raja Zafar; Qureshi, Khalid Mahmood; Khan, Misbahul Islam (Journal of Ayub Medical College Abbottabad, 1999)
This study was designed to see whether there is a circadian variation in the frequency of acute pulmonary edema in diabetic and non-diabetic patients with ischemic heart disease. Total 150 patients (80 diabetics, 70 non-diabetic) of both sexes age range between 34-72 years with the diagnosis of acute pulmonary edema were included in this study. Out of 80 diabetics, 28 had associated hypertension, white 16 patients from non-diabetic group were hypertensive. It was found that there was significant circadian variation in the onset of acute pulmonary> edema in non-diabetic patients but diabetic patients did not exhibit a circadian variation in the onset of acute pulmonary edema